Vascular complications after orthotopic liver transplantation - M. S. Novruzbekov; O. D. Olisov (Трансплантология (Москва), 2017)
Vascular complications (VCs) comprise one of the most serious problems in liver transplantation. This is the next reason of graft loss after primary graft non-function, with the majority of complications being arterial by etiology. VCs significantly decrease the graft and patient survival, contribute to the incidence of retransplantation. This review focuses on the epidemiology, etiology, diagnostics, and treatment of VCs.